The Strategy of Bandung City Department Trade and Industry to Development Small and Medium Industries - Sipahutar, Dayan Hakim Natigor; Maharani, Anggi Putri (SAN Scientific, 2024)
This research aims to determine the influence of Marketing Strategy and Service Quality dimensions on User Satisfaction using quantitative methods and descriptive approaches. The sampling used is probability sampling, namely simple random sampling with a sample size of 100 respondents. The analysis used includes validity testing, reliability testing, classical assumption testing, multiple regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. Research results include that Marketing Strategy and Service Quality has a significant effect on User Satisfaction. Simultaneous calculation results state that Marketing Strategy and Service Quality have a positive and significant influence on User Satisfaction. Based on this analysis, DISDAGIN Bandung City designed a development strategy for Small and Medium Industries. The managerial implication of the relationship between Marketing Strategy and Service Quality dimensions on User Satisfaction is the importance of holistic management that combines these two aspects to increase user satisfaction. Managers need to focus on an in-depth understanding of user needs, developing appropriate marketing strategies, and implementing high service quality to strengthen customer loyalty and brand image.